Pemetaan Perubahan Permukaan Tanah di Kawasan Pulau Nias dengan Menggunakan Data Sentinel - 1A IW: Studi Kasus: Pulau Nias, Provinsi Sumatera Utara - Suseni Hasibuan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The determination of changes in the land surface is an event caused by changes in the volume of the rock layer below. and geological processes such as tectonic and volcanic activity, removal of material from the subsurface such as mining and natural causes such as the occurrence of holes in limestone. The purpose of this study is to determine the magnitude of land surface changes that occur in the Nias Island area caused by earthquakes. The data used in the processing stage with the DinSAR method in 2022 recording, with specifications of dual polarization VV + VH, beam mode IW (interferometric wide) and flight direction ascending. Sentinel 1 data used in this study are 4 pairs of scans, where each pair of scans consists of one scans being the master and another scans being the slave. The master image is the SAR image before the earthquake, while the slave image is after the earthquake. The magnitude of land surface changes that occurred on Nias Island, based on the 2022 earthquake, the largest uplift was the earthquake on December 30, 2022, with a range of values (1.012042) mm with an area of 72,641,981 Hectares. The largest subsidence occurred in the earthquake on December 30, 2022, with a range of values ranging from (-1.373125) mm to (-1.235427) mm with an area of 61347,891 Hectares.